The kuroshio in the Luzon strait - Meunier, Yannek P.
The Luzon strait is the area between the North of Luzon, Philippines and the South of Taiwan. It is the main connection to the Pacific Ocean for the South China Sea (SCS). This region is strongly influenced by the Kuroshio. A scattering of islands (Batanes and Babuyan) found within the Strait play a significant role in the water mixing of the region. Those islands break the Kuroshio intrusion from the Pacific and separate the flow into three main channels, Bashi Channel, Balintang Channel and Babuyan Channel.